[RETRACTED] The Concept of Blockchain-Based Triple Entry Accounting In Indonesia - Nugroho, Tatas Ridho; Setiono, Hari; Ilmiddaviq, Muhammad Bahril (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
This article was retracted due to the author's request